Cutaneous Leishmaniasis (CL): A Cross-Sectional Community Based Survey on Knowledge, Attitude and Practices in a Highly Endemic Area of Waziristan (KPK Province), Pakistan - Irum, Shamaila; Aftab, Malik; Khan, Aisha; Naz, Shumaila; Simsek, Sami; Habib, Ayesha; Ahmed, Haroon (Elsevier, 2021)
Recent outbreaks of Cutaneous Leishmaniasis (CL) in Waziristan make the disease a public health concern in Khyber Pakhtunkhwa (KPK) province, Pakistan. The awareness and behavior of local community towards the disease is an important factor towards effective control and management of CL in endemic areas of Pakistan. A cross-sectional community based survey was piloted in new emerging district of North Waziristan Agency (KPK province), Pakistan from August 2019February 2020. The study aimed to examine the Knowledge, Attitude and Practices (KAP) of the local community members regarding CL. The results revealed that majority of the participants were male. Only 48.2% participants have knowledge about CL and the respondents had a moderate knowledge of CL vector and the disease. Few of the respondents were aware that CL is caused by sand flies, their breeding place, biting time, transmission of CL and control measures. Skin infection and sand-flies were the main disease symptoms and disease vector were known to some of the respondents. Most of the respondents showed positive attitude towards disease seriousness and believed that the disease could be cured and can be treated through modern medicines. Admission to hospitals, cleanliness and use of bed nets were the treatment measures for the disease in suspected patients, whereas some believed that the use of bed nets could be helpful in preventing the leishmaniasis. Moderate knowledge of the CL and its transmission in the study area emphasize the need to initiate health education and awareness campaigns to reduce the disease risk and burden in this highly endemic area in near future.
Keywords: Cutaneous Leishmaniasis; Sand fly; Knowledge; Attitude; Socioeconomic status